2001
DOI: 10.2188/jea.11.170
|View full text |Cite
|
Sign up to set email alerts
|

Regression Analysis of Cancer Incidence Rates and Water Fluoride in the U.S.A. based on IACR/IARC(WHO) Data(1978-1992).

Abstract: Age-specific and age-standardized rates (ASR) of registered cancers for nine communities in the U.S.A. (21.8 million inhabitants, mainly white) were obtained from IARC data (1978-82, 1983-87, 1988-92). The percentage of people supplied with "optimally" fluoridated drinking water (FD) obtained from the Fluoridation Census 1985, U.S.A. were used for regression analysis of incidence rates of cancers at thirty six sites (ICD-WHO, 1957). About two-thirds of sites of the body (ICD) were associated positively with FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 11 publications
2
20
0
1
Order By: Relevance
“…24) Although many epidemiological studies have attempted to correlate cancer mortality with concentrations of F Ϫ in the water supply, no association has been proven. 23,25,26) The present results showed no effect on nucleoside damage and suggest that F Ϫ does not affect any potential cancer risk linked to myeloperoxidase in plasma.…”
Section: Results and Discussion Ph-dependence Of The Reaction Of The mentioning
confidence: 42%
“…24) Although many epidemiological studies have attempted to correlate cancer mortality with concentrations of F Ϫ in the water supply, no association has been proven. 23,25,26) The present results showed no effect on nucleoside damage and suggest that F Ϫ does not affect any potential cancer risk linked to myeloperoxidase in plasma.…”
Section: Results and Discussion Ph-dependence Of The Reaction Of The mentioning
confidence: 42%
“…Further, high doses of fluoride have also been linked to cancer (Marshall 1990). Other experiments carried out in Japan (Tohyama 1996), USA (Takahashi et al 2001) and Taiwan (Yang et al 2000) proved that various types of cancers are associated with fluoride. Further, studies also show that in animals, kidney damage occurs even at lower levels of fluoride exposure over a long time (Manocha et al 1975).…”
Section: Medical Perspectivementioning
confidence: 98%
“…Some laboratory studies of animals have shown evidence of increased osteosarcoma (bone cancer) and osteoma (noncancerous bone tumors), although there is uncertainty in the application of these findings to humans (Doull et al 2006). Studies conducted of human populations have yielded mixed results, including those that suggest a positive association between fluoride ingestion and osteosarcoma (e.g., Hoover et al 1991;Cohn 1992;Yang et al 2000;Bassin 2001;Takahashi et al 2001), those that show no relationship (e.g., Hrudey et al 1990;Mahoney et al 1991;Freni and Gaylor 1992;Grandjean et al 1992;Moss et al 1995;Gelberg et al 1995), and even some that found negative correlations (e.g., McGuire et al 1991;Gelberg et al 1995). Recent work suggests that certain subgroups (e.g., boys aged 6-8) might be more susceptible to the carcinogenic effects of fluoride than the overall population (Bassin et al 2006), but more research is needed to confirm these conclusions (Douglass and Joshipura 2006).…”
Section: Carcinogenic Effectsmentioning
confidence: 99%
“…However, because the cryolite workers were exposed to roughly the equivalent of ingesting water that contains 16 mg/l fluoride, it is not clear how these study results might apply to more typical fluoride exposures. Although there is some evidence of an association between fluoridated drinking water and the incidence of kidney and bladder cancer (e.g., Hoover et al 1991;Yang et al 2000;Takahashi et al 2001), more robust studies are needed to establish this link (Doull et al 2006). Several studies have found evidence for a relationship between fluoride exposure and specific cancers for which no biological causal mechanism is known.…”
Section: Carcinogenic Effectsmentioning
confidence: 99%